Finite Element Analysis On The Effect Of Solder Joint Geometry For The Reliability Of Ball Grid Array Assembly With Flexible And Rigid PCBS - Lau, Chun Sean; Abdullah, M. Z.; Mujeebu, M. Abdul; Yusof, N. Md, (Taylor's University, 2014)

(untitled)
In the present study, three-dimensional (3D) finite element simulation on 132 PIN fleXBGATM package was performed to predict the effect of solder joint geometry on the reliability of Ball Grid Array (BGA) solder joints on flexible and rigid PCBs subjected to thermo-cyclic loading. The commercial FEA tool ABAQUS Version 6.9 was used for the simulations of various shapes of solder joints such as barrel, column and hourglass. Apart from a global modeling, the submodeling analysis technique (local modeling) was also used on the critically affected solder joints, in order to enhance the computation efficiency. The accumulated creep strain and strain energy density were observed for each case, and optimum geometries were obtained. The model was validated with the published experimental data with the minimum percentage error of 3%. It was observed that the hourglass solder joint geometry was very crucial on the reliability of BGA solder joints, and for a given PCB, the optimal choice of hourglass solder joint geometry depended on its rigidity.